تأسيس مفاهيمي لتحولات الأنا في الشخصية الشعرية: Conceptual Foundations for the Transformations of Ego in Poetic Persona - الأستاذ الدكتور فضل الله فضل أحد; براء خالد هلال (Al Manhal Research Journal, 2024)
“Ego” refers to the speaker's identity and the characteristics of their persona. These traits are in constant flux, evolving from one form to another. Philosophers have debated the nature of these transformations within an individual's character. In this research, we delve into the persona of the poet as reflected in their poetry, which isn't necessarily linked to their real personality, as poetry often employs metaphor. We will examine the shifts occurring within the poet's own character and among poets, considering their diverse environments, cultures, and genders. While the Austrian researcher Sigmund Freud discussed the 'self' and its transformations, each thinker viewed it from their perspective. It's found in the philosophies of Hegel, Descartes, Kant, Erikson, Wilber, Kohut, Nietzsche, and Maslow. This subject occupies more than a third of the renowned poet Muhammad Iqbal's work. This is a critical study employing a psychological approach.